Variability of sedation practices in palliative care unit in France: a six units retrospective analysis - Gary Pommier; Matthieu Frasca; Lydie Chain; Simon Piroddi; Kevin Legueult; Flora Tremellat-Falière; Guillaume Economos (BMC Palliative Care)
Abstract Background Palliative sedation is the monitored use of medications intended to reduce consciousness to relieve the burden of otherwise intractable suffering. Since 2016, the French Leonetti-Claeys law has granted patients the right to receive continuous deep sedation until death (CDSUD) for some indications. There are relatively few data in the literature assessing sedation practices in palliative care units (PCUs). Methods This study aimed to compare sedation practices in six French PCUs, analyzing the frequency, types of sedation (CDSUD vs. proportional sedation), and use of sedative medications during the last 72 h of life. This retrospective study examined the data of patients who died in these units between July and December 2021. Results The results revealed statistically significant variability in sedation practices. The overall prevalence of sedation practices (all types) was 22%. The prevalence for CDSUD was 12%. Some units had much higher or lower rates of sedation, suggesting differences in the interpretation of guidelines and regulations, possibly because of cultural or individual factors within the units. The study also found important variability in the use of sedative medication in terms of molecules and dosage. Midazolam was the most commonly used benzodiazepine but the dosage varied significantly depending on the units. Conclusions Further qualitative research is needed to understand the reasons for the observed variability in sedation practices and improve the standardization and clarity of palliative sedation.